Role of angiopoietin-like 4 in tumor growth. - Zhu, Pengcheng. (2011)
Cancer is a leading cause of death worldwide. Tumor cells exploit various signaling molecules to promote their growth and metastasis. The angiopoietin-like 4 protein (ANGPTL4) has well-studied roles in metabolism, yet its role in cancer biology remains undefined. Herein, by using human tumor tissue arrays, tumor cell lines and human skin tumor samples, we found that elevated ANGPTL4 expression is widespread in most known tumor types. Treating cancer cells with ANGPTl4-targeted RNAi or monoclonal antibodies imparts a significant decrease in in vivo tumor growth and induces apoptosis in cancer cell lines upon anoikis challenge. Mechanistic investigation suggests that tumor-derived ANGPTL4 interacts with integrins to stimulate the NADPH oxidase-dependent production of O2-. A high ratio of O2-:H2O2 oxidizes/activates Src, triggering the PI3K/PKBα and ERK pro-survival pathways to confer anoikis resistance, thus promoting tumor growth. ANGPTL4 deficiency results in diminished O2- production and a reduced O2-:H2O2 ratio, creating a cellular environment conducive to apoptosis. In all, we show that enhanced expression of ANGPTL4 is common in tumors, and tumor-derived ANGPTL4 activates integrin-related, oxidant-dependent survival pathways, despite the loss of matrix attachment, suggesting ANGPTL4 as an important novel player in redox-mediated cancer progression. Our findings suggest that anticancer strategies focusing on redox-based apoptosis induction in tumors are viable.